ANALISIS PENGGUNAAN APLIKASI TIKTOK PADA ANAK USIA DINI DI MASA PANDEMI - Elisa Intania; Velly Flaviani Hyunanda; Jejen Zainal Muttaqin (Widya Komunika, 2022)
This research is entitled “The Effects of the Use of TikTok Application on Young Children During Pandemic”. The purpose of this research is to increase knowledge of the importance of the role of parents, mental health of young children, and the awareness of the effects of using TikTok application. The research method used is through phenomenological research and qualitative research. The data collection techniques used for this research is by distributing questionnaires and online interviews. The interviews conducted involves several parents who uses TikTok application. Based on the results received, there has been an increase of social media usage, in particular the TikTok application. The TikTok application caused an adverse effect on young children. Furthermore, there has been some concerns from several parents during interviews over the mental health issues of young children. The presence of TikTok as a new media has caused rapid cultural shift and can be easily imitated by young children. The suggestions conveyed through this article is the importance of the role of parents in accompanying and supervising their young children in using TikTok, increase awareness of parents on the use of TikTok application, and the adverse effects on young children when using the TikTok application.